Carles Salvador en la cruïlla de la recuperació poètica valenciana - Carbó, Ferran (Caplletra. Revista Internacional de Filologia, 2015)
Carbó reviews every book of poetry by Carles Salvador from Plàstic (1923), to El fang i l’esperit (1952), through which he traces –in both general and specific terms– the evolution of Salvador and his contributions to the renovation of Valencian lyrics in Catalan during the crucial decades.